Sustainable Land Use and Climate Change in Belgrade - The Role of Urban Gardens - Miljković, Jelena Živanović; Pantić, Marijana; Čepić, Slavica (European Journal of Sustainable Development, 2023)
Population growth and urban sprawl are expected to continue increasing pressures on agricultural land, green infrastructure and climate change’s impact on the urban environment. Accordingly, the challenge of securing sustainable land use and climate change mitigation needs to be confronted in cities globe wide. Urban green areas represent an asset of public interest with multiple roles – they are recreational zones, noise and pollution protection belts, areas with aesthetic, social and curative values as well as an infrastructure for combating climate change. All these functions accentuate the relevance of urban gardens in urban development, for which their preservation and development play an irreplaceable role in cities. This paper analyses a specific form of urban gardens in Belgrade (“baštenske kolonije” or “garden colonies”) with a focus on urban land use planning. The research methodology consists of a literature and document review and systematic analysis. The study includes legislative in Serbia and urban planning documents in Belgrade, with the goal being to identify governmental and planning attitude towards urban gardening and their recognition of ecosystem services and climate change combat. The preliminary results indicate that this form of sustainable land in Belgrade is left to the spontaneous actions of individuals with no legally defined status in the previous period Keywords: sustainable land use, urban gardens, climate change, urban planning, Belgrade.